The landscape of immunogenic cell death-related genes predicts the overall survival and immune infiltration status of non-small-cell lung carcinoma - Jian Zhang; Huiying Li; Xi Zhang; Yue Yang; Yue Sun (Heliyon)
Background: Non-small cell lung cancer (NSCLC), which accounts for about 85 % of all lung cancers, currently exhibits insensitivity to most treatment regimens. Therefore, the identification of new and effective biomarkers for NSCLC is crucial for the development of treatment strategies. Immunogenic cell death (ICD), a form of regulated cell death capable of activating adaptive immune responses and generating long-term immune memory, holds promise for enhancing anti-tumor immunity and offering promising prospects for immunotherapy strategies in NSCLC. Methods: Clinical information and expressive profiles of NSCLC genes were retrieved from the GEO and TCGA databases. By combining these databases, the researchers were able to identify the appropriate genes for use in forecasting outcomes of patients with this type of cancer. We further performed functional enrichment, gene variants and immune privilege correlation analysis to determine the underlying mechanisms. This was followed by univariate and multivariate Cox regression and LASSO regression analyses, we developed a prognostic risk model based on the TCGA cohort, which included 17 gene labels. The results of the external validation were then used to identify the appropriate genes for use in predicting the survival outcome of patients with this type of cancer. In addition, a nomogram was created to help visualise the clinical presentation of the patients. For the analyses, we performed 50 functional and immunoinfiltration assessments for two risk groups. Results: Using 17 genes (AIRE, APOH, CDKN2A, CEACAM4, COL4A3, CPA, DBH, F10, FCGRB, FGFR4, MMP1, PGLYRP1, SCGB2A2, SLC9A3, UGT2B17 and VIP), The researchers then created a gene signature that could be used to identify patients with an increased risk of contracting cancer. They divided the patients into two groups based on their risk score. The low-risk group exhibited a better prognosis (P < 0.01). The survival curve demonstrated that ICD-related models could accurately predict patient prognosis. Conversely, high-risk subgroups were closely associated with immune-related signaling pathways. The analysis of immune infiltration also showed that the infiltration levels of most immune cells were higher in the high risk sub-group than in the low risk sub-group. In comparison to the low-risk group, the high-risk group was more susceptible to the immune-checkpoint blockade (ICB) treatment. Conclusion: Our researchers utilized a gene model to analyze the immune inflammation and prognosis of patients with non-small-cell lung cancer (NSCLC). The discovery of new ICD-related genes could lead to the development of new targeted treatments for this condition.